Analogical City - McEwan, Cameron (punctum books, 2024)
In Analogical City, Cameron McEwan argues for architecture’s status as a critical project. McEwan revisits architect Aldo Rossi as a paradigmatic figure of the critical rational tradition, studying a neglected aspect of his thought — the analogical city — to excavate its potential. McEwan develops a grammar of the analogical city under the headings of Imagination, Transformation, City, Multitude, and Project. McEwan argues that the analogical city is critical, collective, and emancipatory. Analogical thought and understanding cities as analogical might open the conditions of possibility for rethinking the critical project in architecture.